RUMUSAN DELIK DAN FORMULASI KETENTUAN PIDANA QANUN ACEH NOMOR 12 TAHUN 2003 TENTANG KHAMAR DALAM PERSPEKTIF KEBIJAKAN HUKUM PIDANA. - Khairilina, Suhaimi, Dahlan Ali. (Jurnal Ilmu Hukum, 2015)
Abstract:The elements of crime in the Khamar (alcoholic drink) Local Law Number 12, 2003 in Article 6 states that (1) Everyone or an institution is forbidden to produce, provide, sell, import, distribute, transport, keep, dump, gift, alcoholic drink and its similar products (2) Everyone or an institution is forbidden to take a part in order to produce, provide, sell, import, distribute, transport, keep, dump, gift, alcoholic drink and its similar product. Article 55 of Indonesian Penal Code states that: (1) punished as a violator: 1.Perpetrator, commander, accompanier the crimes. Article 56 of the Code states that punished as an abettor: 1. those who provide an aid of crime being committed, give an opportunity, facility, or info of committing crime. Based on Article 6 (1) and (2) of the local law there is a repetition of crime as the punishment is similar that is imprisonment. The Local Law Number 12, 2003 regarding Khamar, in Article 26 has several criminal elements that are namely:1) everyone is forbidden to consume it and its similar kinds. 2) The forbidden are to produce, provide, sell, import, distribute, transport, keep, dump, gift, alcoholic drink. 3) The 40 times of whipping for who consume and imprisonment maximally 1 year and the minimally 3 months or fine IDR. 75.000.000, and it is minimally IDR. 25.000.000. The Law has not provided clear information of the elements. Keywords :Crime Elements, Criminal Law Formulation, Criminal Law Policy. Abstrak: Rumusan delik Qanun Khamar Nomor 12 Tahun 2003 dalam Pasal 6 menyebutkan: (2) Setiap orang atau badan hukum dilarang turut serta/membantu memproduksi, menyediakan, menjual, memasukkan, mengedarkan, mengangkut, menyimpan, menimbun, memperdagangkan, menghadiahkan dan mempromosikan minuman khamar. Pasal 55 KUHP menyebutkan: (1) Dipidana sebagai pelaku tindak pidana : 1. mereka yang melakukan, yang menyuruh melakukan, dan yang turut serta melakukan perbuatan;Berdasarkan isi Qanun pasal 6 ayat (2) terdapat pengulangan delik, karena ketentuan pidana sama yaitu penjara. Qanun Aceh Nomor 12 Tahun 2003 tentang khamar, Pasal 26 di dalamnya memuat beberapa unsur tindak pidana, yaitu: 1). Setiap orang dilarang mengkonsumsi minuman khamar. 2). Yang dilarang: memproduksi, mengedarkan, mengangkut, memasukkan, memperdagangkan, menyimpan, menimbun dan mempromosikan. 3). Ancaman pidana 40 kali cambuk bagi yang mengkonsumsi, dan ‘uqubat ta’zir berupa kurungan paling lama 1 tahun, paling singkat 3 bulan dan/atau denda paling banyak Rp. 75.000.000,-, paling sedikit Rp. 25.000.000. Dalam Qanun tersebut ada beberapa unsur tindak pidana yang tidak tegas. Kata Kunci ;Rumusan Delik, Formulasi Ketentuan Pidana, Kebijakan Hukum Pidana.